ПЕДАГОГІЧНІ УМОВИ ФОРМУВАННЯ МУЗИЧНИХ ІНТЕРЕСІВ МОЛОДШИХ ШКОЛЯРІВ НА УРОКАХ МУЗИКИ (Педагогіка вищої та середньої школи, 2010)
The article deals with the pedagogical conditions that contribute to the successful formation of musical interests of junior schoolchildren in music lessons.